2022
DOI: 10.1007/s10266-022-00738-0
|View full text |Cite
|
Sign up to set email alerts
|

Modification of glass-ionomer cement properties by quaternized chitosan-coated nanoparticles

Abstract: Glass ionomers (GICs), because of their qualities, are in a good position to be modified to resist masticatory stresses as permanent posterior restoration and prevent recurrent caries. The purpose of the present study was to evaluate the effect of adding quaternized chitosan-coated mesoporous silica nanoparticles (HTCC@MSNs) to conventional GIC on its mechanical properties, antimicrobial activity and fluoride release and the effect of 1- and 3-month water aging on the studied properties. HTCC@MSNs was synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In this study, chitosan-modified RMGICs groups release greater rates of fluoride than control RMGIC, the same result as a recent study, which reported that the inclusion of chitosan in RMGIC increased fluoride release [35]. Chitosan also enhanced fluoride release in conventional GIC [16,36].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, chitosan-modified RMGICs groups release greater rates of fluoride than control RMGIC, the same result as a recent study, which reported that the inclusion of chitosan in RMGIC increased fluoride release [35]. Chitosan also enhanced fluoride release in conventional GIC [16,36].…”
Section: Discussionsupporting
confidence: 87%
“…Some studies have reported the antibacterial properties of chitosan-modified GIC cement [13,14]. Recently, chitosan in various forms has been studied to improve some properties of GIC, such as increasing osteogenic potential in osteosarcoma cells [15] and adding quaternized chitosan-coated mesoporous silica nanoparticles in order to improve mechanical properties, increase fluoride release, and enhance antibacterial effects [16].…”
Section: Introductionmentioning
confidence: 99%
“…E. A. Elshenawy et al demonstrated the effect of quaternized chitosan-coated mesoporous silica nanoparticles on GIC. 109 An increased bacterial inhibition zone and fluoride release kinetics of GIC were reported. Table 2 summarises different modifications of polyalkenoic acid and glass powder to improve the mechanical and antimicrobial properties of GIC.…”
Section: Effects Of Antimicrobial Activity Of Polyalkenoic Acids On Gicmentioning
confidence: 99%
“…The effects of the substitute chain length, and the grafting ratio of QAS on polyalkenoic acid for their antibacterial and mechanical properties were investigated D. Xie et al 116 Effects of quaternized chitosan coated nanoparticles on GIC Bacterial inhibition zones and fluoride release increased proportionally to the amount of filler added. Mechanical properties were improved E. A. Elshenawy et al 109 The study aimed to develop antibacterial GIC containing a quaternary ammonium salt (dimethylaminododecyl methacrylate, DMADDM) to improve the antimicrobial properties GIC containing DMADDM improved the physicochemical and antibacterial properties. Modified GIC improved the management of secondary caries S.-P. Wang et al 117 Evaluation of the effect of magnesium oxide nanoparticles (MgO) on the antibacterial and antibiofilm formation of GIC (3M ESPE Ketac Molar)…”
Section: Materials Advances Reviewmentioning
confidence: 99%
“…There was a lack of both the 2915 and 1399 cm -1 bands. C-H bending in -N(CH 3 ) 3 is indicative of NH 2 group quaternization in chitosan structure (41), the characteristic peak at 3446 cm − 1 was O-H stretching vibration band.…”
Section: Ftir Analysismentioning
confidence: 99%